OPTIMALISASI KADER DALAM PENCEGAHAN COVID 19 DI DESA PASIR LOR KECAMATAN KARANGLEWAS BANYUMAS - Sumarni, Sumarni; Indrayani, Eni (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
Corona virus Disease 2019 (COVID-19) is a new type of disease that has never been identified before in humans. COVID 19 can be transmitted from human to human through coughing / sneezing (droplet). To prevent the spread of infection is through regular hand washing with soap and clean water, applying the ethics of coughing and sneezing, avoiding direct contact with livestock and wild animals and avoiding close contact with anyone who shows symptoms of respiratory illnesses such as coughing and sneezing. The objective of this activity is to increase the knowledge and skills of cadres about prevention of Covid 19 through Covid 19 prevention training. The method to be used to realize this program is through preparation, implementation, evaluation and follow-up plans. The results showed cadres who had good knowledge increased from 16% to 40%, while cadres mothers who had sufficient knowledge increased from the previous 24% to 32%. Cadres who have less knowledge have decreased from 60% to 28%. Conclusion; the optimization of health cadres in the prevention of Covid 19 in Pasir Lor Village took place effectively and efficiently.Â Keywords: Optimization of cadres; Covid-19 preventionÂ